2020
DOI: 10.1002/bkcs.12103
|View full text |Cite
|
Sign up to set email alerts
|

Lithium Bromide/HBpin: A Mild and Effective Catalytic System for the Selective Hydroboration of Aldehydes and Ketones

Abstract: The catalytic hydroboration of aldehydes and ketones with HBpin was examined using simple and commercially available metal salts (Li, Na, and K). Among the tested salts, LiBr (0.5-1.0 mol%) was found to be an efficient catalyst for the hydroboration of various aldehydes and ketones at room temperature. Further, the chemoselective hydroboration of aldehydes over ketones was also demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…Analogous studies in tetrahydrofuran were proposed to result in a complex equilibrium between several different boron-containing species in which the trialkoxy­borohydride, [( t BuO)­B­(H)­pin] − , was the major species participating in hydride delivery (Scheme ). On the basis of this precedent, a number of closely related studies have been described during the last decade, derived variously from the use of NaOH, n BuLi, (also imines, alkynes, nitriles, and carbodiimides), , NaH, KH, Li­[O t Bu], K­[O t Bu], K 2 CO 3 , KCH 2 Ph, M­[N­(SiMe 3 ) 2 ] (M = Li, Na, K), LiBr, , MF (M = K, Cs), 2,6-di- tert -butylphenolate lithium, 1,1-dilithioferrocene, ( Dipp Nacnac)­Li, and l-lithio-2-alkyl-1,2-dihydropyridine . In a very recent advance, Newman and Melen have shown that the simple bases, lithium di- iso -propylamide and tert- butoxide catalyze the hydroboration of ketones, but with some enantioselectivity (er up to 70:30) when used in conjunction with enantiopure BINOL-type ligands .…”
Section: Molecular Hydrides Of the Group 1 Metalsmentioning
confidence: 99%
“…Analogous studies in tetrahydrofuran were proposed to result in a complex equilibrium between several different boron-containing species in which the trialkoxy­borohydride, [( t BuO)­B­(H)­pin] − , was the major species participating in hydride delivery (Scheme ). On the basis of this precedent, a number of closely related studies have been described during the last decade, derived variously from the use of NaOH, n BuLi, (also imines, alkynes, nitriles, and carbodiimides), , NaH, KH, Li­[O t Bu], K­[O t Bu], K 2 CO 3 , KCH 2 Ph, M­[N­(SiMe 3 ) 2 ] (M = Li, Na, K), LiBr, , MF (M = K, Cs), 2,6-di- tert -butylphenolate lithium, 1,1-dilithioferrocene, ( Dipp Nacnac)­Li, and l-lithio-2-alkyl-1,2-dihydropyridine . In a very recent advance, Newman and Melen have shown that the simple bases, lithium di- iso -propylamide and tert- butoxide catalyze the hydroboration of ketones, but with some enantioselectivity (er up to 70:30) when used in conjunction with enantiopure BINOL-type ligands .…”
Section: Molecular Hydrides Of the Group 1 Metalsmentioning
confidence: 99%
“…Out of all tested substrates, only hydroboration of aldehydes and ketones provided the desired products. With as little as 0.5–1 mol % of LiBr, various substrates bearing aliphatic and aromatic substituents were reduced under mild reaction conditions and in short reaction times …”
Section: Hydroboration Of Polarized Unsaturated Bondsmentioning
confidence: 98%
“…Thus, excellent yields were obtained for a wide range of N-aryl ketimines. Furthermore, after successfully applying lithium bromide for hydroboration of aldehydes and ketones in the presence of cheap and readily available lithium bromide 53, 97 An et al utilized this catalytic system for hydroboration of imines. Various aryl-protected aldimines and ketimines were hydroborated to afford the corresponding amines under mild reaction conditions and in remarkably short reaction times.…”
Section: Iminesmentioning
confidence: 99%
See 2 more Smart Citations